Conflict and its Impacts on Women’s Political Representation in Nepal - Thapa, Prema Bista (NCWA Annual Journal, 2025)
Nepal went through immense socio-political transformation in the last three decades since the Maoist armed conflict which has had a significant role in establishing the issues of the marginalized population and women. Socio-cultural barriers and inequalities, violence and the patriarchal nature of society have often hindered women’s empowerment. The promulgation of the Constitution in 2015 has ensured women’s representation in politics and governance to promote gender equality. Although this is a positive step, more efforts are needed to enhance women’s representation in politics at the key decision-making levels. This article explores the intricate relationship between the conflict and women’s political representation in Nepal particularly in the context of the decade-long armed conflict (1996-2006) and its aftermath. It further examines the significance of these changes in women’s political leadership and how significant barriers remain that must be addressed to ensure sustained participation and representation of women in the country’s political landscape.